Economic Impacts of the U.S. Sugar Corporation in Florida: Implications of the Purchase by the State of Florida - Alan W. Hodges; W. David Mulkey; Thomas H. Spreen; Rodney L. Clouser (EDIS)
FE754, a 10-page illustrated report by Alan W. Hodges, W. David Mulkey, Thomas H. Spreen, and Rodney L. Clouser, evaluate the economic impacts of the current operations of USSC and the potential impact under the proposed purchase, based on publicly available information from the company’s website (http://www.ussugar.com) and other sources. Includes references. Published by the UF Department of Food and Resource Economics, October 2008.